Strengthening School Counselor Capacity in Implementing The Pancasila Learner Profile Through Guidance and Counseling Program - Awalya Siska Pratiwi; Muslihati; Zen, Ella Faridati; Sobri, Ahmad Yusuf; Achmad Miftachul Ilmi; Khusnul Khowatim (Community Development Journal, 2023)
This service is motivated by the non-optimal implementation process of Strengthening the Pancasila Student Profile among school counselors. Strengthening the profile of Pancasila students is one of the government programs in the context of an independent curriculum. This effort is urgent to strengthen the noble character of students to become a figure of faith and piety, think critically, creatively, independently, have a broad view and be able to adapt to diversity in Indonesia and the global context, be responsible for all attitudes and actions. All teachers in various types and levels of education are the frontline stakeholders in strengthening the Pancasila learner profile, including at the Madrasah Tsanawiyah level, both public and private, so teachers must understand the nature and purpose of this program as well as be capable and competent in implementing various strategies and educational techniques to strengthen the Pancasila learner profile. It is very important to strengthen the Pancasila learner profile in students so that Indonesian youth are ready to face the challenges of the Demographic Bonus and global competition. The implementation of service activities is carried out using the 6P method, namely; (1) preparation stage; (2) material preparation stage; (3) socialization stage; (4) training stage; (5) closing stage; and (6) reporting stage. With the application of the Twin-Cycle Experiential Learning Model method, it is hoped that it will be able to foster the character of educators in the application of the Pancasila student profile in schools based on the 6 dimensions of the student profile character.